Bandgap-adjustment and enhanced surface photovoltage in Y-substituted LaTaIVO2N. Issue 23 (8th June 2020) - Bubeck, Cora; Widenmeyer, Marc; De Denko, Alexandra T.; Richter, Gunther; Coduri, Mauro; Colera, Eduardo Salas; Goering, Eberhard; Zhang, Hongbin; Yoon, Songhak; Osterloh, Frank E.; Weidenkaff, Anke
Abstract : Microstructure controlled ammonolysis allowed the synthesis of oxynitrides La1− x Y x Ta IV O2 N ( x ≤ 0.3) and YTa(O, N)3 of which the first ones showed a remarkable up-built of photovoltage even in the presence of reduced tantalum ( e.g. Ta 4+ ). Abstract : Perovskite-type oxynitrides AB (O, N)3 are photocatalysts for overall water splitting under visible light illumination. In the past, structurally labile perovskite-type oxynitrides ( e.g. YTaON2 ) were predicted to be highly suitable. In this work, we tackle the challenging YTa(O, N)3 synthesis by Y-substitution in LaTa IV O2 N resulting in phase-pure La0.9 Y0.1 Ta IV O2 N, La0.75 Y0.25 Ta IV O2 N, and La0.7 Y0.3 Ta IV O2 N. By using microcrystalline YTaO4 together with an unconventional ammonolysis protocol we synthesized the highest reported weight fraction (82(2) wt%) of perovskite-type YTa(O, N)3 . Ta 4+ in La1− x Y x Ta IV O2 N was verified by X-ray photoelectron spectroscopy (XPS) and X-ray near edge absorption structure (XANES) analysis. Density functional theory (DFT) calculations revealed a transparent conductor-like behavior explaining the unusual red/orange color of the Ta 4+ -containing perovskites. In combination with crystal structure analysis the DFT calculations identified orthorhombic strain as the main descriptor for the unexpected trend of the optical bandgap ( E G, x =0.3 ≈ E G, x =0 < E G, x =0.1 < E G, x =0.25 ). Surface photovoltage spectroscopy (SPS) of particulate La1− x Y x Ta IV O2 N ( x = 0, 0.1, 0.25, 0.3) films revealed negative photovoltages at photon energies exceeding 1.75 eV, confirming that these materials are n-type semiconductors with effective bandgaps of ∼1.75 eV irrespective of the Y content. The photovoltage values increased with the Y content, suggesting an improved carrier generation and separation in the materials. However, increasing the Y content also slowed down the timescales for photovoltage generation/decay indicating trap states in the materials. Based on our results, we suggest a significantly weaker as classically assumed impact of reduced B -site metal cations such as Ta 4+ on the photovoltage and charge carrier recombination rate.